FEMINIST THOUGHT IN VIRGINIA WOOLF’S A ROOM OF ONE’S OWN AND THREE GUINEAS - Ms Savita, Ms.Amandeep Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This research focuses on the writer's selection of themes and the type of person who lives in that area A lot of things are talked about in Woolf's book: feminism, financial independence, mental freedom, and the difficulties that women may have in their relationships with men, whether they're husbands or friends. In her essay "A Room of One's Own," for example, Woolf talks about how women aren't allowed to go to school and how this affects their income. Strong political action is what Woolf wants people to do in "Three Guineas" to fight fascism and the move toward war. In addition to the analysis, this research gives a very detailed account of the views of critics who have already said what they think opinions on the subject.